Accelerating Digital Transformation in Islamic Banking - Julius Gofinda Prasta (Arthatama: Journal of Business Management and Accounting, 2024)
The rapid advancement of digital technology has revolutionized the banking sector, necessitating the adoption of digital banking services to enhance operational efficiency and customer experience. This study examines the digital transformation process in Indonesia's Islamic banking industry, highlighting key challenges, regulatory frameworks, and the impact of technological innovation. Using a systematic literature review, the research identifies the factors influencing digital adoption, including trust, regulatory compliance, and customer satisfaction. Findings indicate that the Covid-19 pandemic has accelerated digital banking adoption, prompting Islamic banks to expand their digital services to remain competitive. The study underscores the importance of regulatory support, technological innovation, and customer trust in facilitating a seamless transition toward fully digital Islamic banking. Future research should explore the role of artificial intelligence, blockchain, and fintech collaborations in shaping the industry's trajectory.